Analisis Dampak Kepercayaan Diri Terhadap Kemampuan Berbicara Siswa di SD - Ajeng Kinanti; Adrias Adrias; Salmaini Safitri Syam (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
Speaking skills are very important skills for students to master in an era of increasingly high demands. However, there are still many students who experience difficulties in speaking. The main factor that influences speaking ability is the level of self-confidence in students. The purpose of this research is to analyze the impact of self-confidence on students' speaking abilities and to find ways to overcome these problems. The research method used is a qualitative method using interview data collection techniques and literature studies. Interviews were conducted with teachers to obtain empirical data regarding the relationship between self-confidence and students' speaking abilities, while literature studies were used to strengthen the findings with relevant theories. The research results show that students with high self-confidence will actively speak and be able to express their ideas and opinions clearly. Meanwhile, students with low self-confidence will find it difficult to speak to express their thoughts or have the courage to speak in public. Speaking skills greatly influence students' activity during the learning process so that if left untreated it will hinder their academic and social development.